Mendelian Randomization and Transcriptomics Analysis Reveal Potential Relationships Between Lipids, Immune Cells and PCOS - Xie Y; Zhang Z; Zhao Y; Zhang J; Yin Q (International Journal of Women's Health)
Yafei Xie, Zelin Zhang, Yuanyuan Zhao, Jiali Zhang, Qiaozhi Yin School of Clinical Medicine, Chengdu University of Traditional Chinese Medicine, Chengdu, Sichuan, People’s Republic of ChinaCorrespondence: Qiaozhi Yin, Email QiaozhiYin2024@hotmail.comBackground: It has been noted that plasma lipid levels are closely associated with polycystic ovary syndrome (PCOS). Immune cells have also been recognized as critical indicators for evaluating the impact of lipids on disease progression. However, there is still a lack of conclusive causal evidence as to whether immune cells mediate the relationship between lipids and PCOS.Methods: This study used a two-step two-sample Mendelian randomisation (TSMR) analysis to explore the causal relationship between plasma lipid groups and PCOS, and the mediating role of immune cells in this relationship. Transcriptome analysis was used to further explore the relationship between lipid metabolism, immunity, and PCOS.Results: The inverse variance weighted (IVW) method and Bayesian weighted Mendelian randomized (BWMR) method identified six plasma lipid groups that exhibited causal effects on PCOS, with no evidence of reverse causality. Eighteen immune cell traits are strongly associated with PCOS. TSMR analysis identified SSC-A on CD4+ as the key factor mediating the causal association of PC (0:18:1_20:4) and PI (18:1_18:2) with PCOS, with mediating effects of − 0.003 (95% CI [− 0.017, 0.012]) and 0.003 (95% CI [− 0.021, 0.026]), respectively. Functional enrichment analysis revealed that PCOS was strongly associated with numerous immune pathways. Immune infiltration evaluation results indicated significant disparities in the distribution of a substantial number of immune cells, especially for all types of CD4+ T cells. Furthermore, Metabolic inference analysis revealed that fatty acid biosynthesis is closely related to PCOS.Conclusion: Our results provide genetic and transcriptomic evidence substantiating the potential relationship between lipids, immune cells, and PCOS. CD4+ T cells might be key mediators in the causal association between lipids and PCOS. Comprehending this relationship could enhance treatment and prevention strategies for PCOS through the comprehensive management of lipid irregularities. Further experimental studies are required to elucidate the detailed mechanisms involved in this relationship.Keywords: plasma lipid, immune cell, polycystic ovary syndrome, Mendelian randomization, transcriptomics analysis